"The Biological Social Revolution of Contemporary Human" - Al-Saleh, Iman (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research is considered as a theoretical attempt, to know the aspects of biological evolution & it's reflect on the humanitarian philosophical side, specially which related to ethical & educational values In this research we refer to the productive dialectical relation between human & nature, which is considered as an ethical process, based on active & effective participation with nature, to achieve the human being goals. The man in general is considered as a main part of universal nature activity, which we try to show this process in being Finally we try to know the effective position of human & his rule in cosmic that he belong to it, as an important goal of other humanity goals